2019
DOI: 10.1055/s-0039-1696639
|View full text |Cite
|
Sign up to set email alerts
|

Management of Lifestyle Factors in Individuals with Cirrhosis: A Pragmatic Review

Abstract: Lifestyle-related factors are major determinants/modifiers of prognosis in patients with cirrhosis. Accumulating evidence indicates that malnutrition, obesity, sedentary lifestyle, alcohol and smoking habits, and likely poor oral hygiene can increase the risk of progression of the disease, and some of them are linked to higher risk of hepatocellular carcinoma. Importantly, lifestyle-related factors can be largely corrected, and as such they represent an attractive approach to be added to etiological and pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 103 publications
0
15
0
2
Order By: Relevance
“…Our study indicated that alcohol use attributed LC deaths doubled from 1990 to 2019, whereas the related ASDR slightly decreased during this period. This discrepancy might be the result of the acceleration of population aging worldwide [21,22]. Globally, alcohol consumption is roughly consistent with the distribution of alcohol use-related LC burden [24].…”
Section: Discussionmentioning
confidence: 66%
“…Our study indicated that alcohol use attributed LC deaths doubled from 1990 to 2019, whereas the related ASDR slightly decreased during this period. This discrepancy might be the result of the acceleration of population aging worldwide [21,22]. Globally, alcohol consumption is roughly consistent with the distribution of alcohol use-related LC burden [24].…”
Section: Discussionmentioning
confidence: 66%
“…Currently, there are few therapeutic opportunities for liver fibrosis and the introduction of efficient options needs to be addressed. Suppression of viruses, dietary alterations, decreasing body weight in NAFLD, and induction of fibrosis regression are proposed to stop the disease progression (Kohla et al, 2020;Sheka et al, 2020;Tandon and Berzigotti, 2020). The current clinical trials mostly did not focus on the direct modification of the mechanisms of the disease progressions but investigated other mechanistic approaches such as the causative agents in the underlying liver damage, the received signals from other organs, metabolic pathways, immune system, and cell death processes.…”
Section: Molecular Mechanism Of Liver Fibrosis and Recent Clinical Trialsmentioning
confidence: 99%
“…The risk of developing sarcopenia is associated with male gender, ascites, and the degree of renal and hepatic dysfunction[ 9 ]. Overweight and obesity are as frequent as in general population, ranging from 20% to 40% and aggravating prognosis both in compensated and in decompensated cirrhosis[ 11 ]. Sarcopenic obesity (coexistence of sarcopenia and obesity) is present in one-fifth to one-third of patients with cirrhosis.…”
Section: Clinical Significance and Consequences Of Sarcopeniamentioning
confidence: 99%